Metal Hypersensitivity in Orthodontic Patients - Sandhya Maheshwari Sanjeev K; Verma Sushma Dhiman (Mashhad University of Medical Sciences, 2015)
Orthodontic treatment of individuals with metal hypersensitivity is a matter of concern for the orthodontist. Orthodontic appliances contain metals like Nickel, Cobalt and Chromium etc. Metals may cause allergic reactions and are known as allergens. Reaction to these metals is due to biodegradation of metals in the oral cavity. This may lead to the formation of corrosion products and their exposure to the patient. Nickel is the most common metal to cause hypersensitivity reaction. Chromium ranks second among the metals, known to trigger allergic reactions. The adverse biological reactions to these metals may include hypersensitivity, dermatitis and asthma. In addition, a significant carcinogenic and mutagenic potential has been demonstrated. The orthodontist must be familiar with the best possible alternative treatment modalities to provide the safest, most effective care possible in these cases. The present article focuses on the issue of metal hypersensitivity and its management in orthodontic